Productivity of Urochloa humidicola in different doses of nitrogen and potassium in the region of Vale do Jamari, Rondônia, Brazil (Research, Society and Development, 2023)
This study aims to determine the productivity of Urochloa humdicola on different doses of nitrogen and potassium fertilization in a pasture in the city of Cacaulândia, in the Vale do Jamari region. The experimental design was in randomized blocks with four replications and consisted of two experiments, the first being only with nitrogen fertilization with the following doses: 0; 50; 100; and 150 kg ha-1 of N. The second was performed by combining nitrogen with potassium as follows: 0/0; 50/30; 100/50; and 150/80 kg ha-1 of N/ kg ha-1 of K2O. In addition, phosphate fertilizer was applied throughout the area at a dose of 60 kg/ha P2O5, as recommended for fertilization of group lll grasses. The research took place between October 2020 and March 2021.The cuts were made respecting a residue of 10 cm from the soil level, using scissors and knife, with care not to have loss of material, for processing and obtaining the results, the first cut was made at 30 days and the second 70 days after the first fertilization, allowing the counting of total tillers. It was possible to conclude that both nitrogen fertilization and the combination of nitrogen and potassium, caused the analyzed parameters to show growth in production according to the dosage.